Transcending Fixed Infrastructure: Leveraging Mobile RSUs for Dynamic Collective Perception Services in VANETs - Thenuka Karunathilake; Anna Forster (IEEE Access)
Road safety has become a major concern in recent decades due to the growing number of vehicles, which is expected to double in the next decade. This increase is likely to result in more accidents and greater financial costs due to traffic congestion. Vehicular Ad Hoc Networks (VANETs) offer a promising solution to address these issues by facilitating information exchange, thereby enhancing situational awareness. One of the key VANET safety applications, Collective Perception (CP) services, aims to improve awareness of both V2X and non-V2X objects during the transition period before full V2X vehicle market penetration. Traditionally, Collective Perception Messages (CPMs) are generated by V2X vehicles or specialized Road Side Units (RSUs) equipped with sensors and are shared with other V2X vehicles within a single-hop communication range. This work proposes using mobile RSUs to disseminate RSU-assisted CPMs by aggregating received CPM objects, rather than relying on conventional fixed RSUs. The mobility of RSUs can increase the chances of distributing CPMs to a larger number of vehicles, thereby enhancing overall situational awareness. Additionally, we introduce a novel dynamic CPM generation mechanism for RSU-assisted CPMs, which adjusts the CPM dissemination rate based on the current environment, reducing channel load compared to the traditional periodic CPM generation approach. We begin by conducting simulations in a city scenario to evaluate the performance of fixed and mobile RSU-assisted dissemination methods. We explore the critical question of whether mobile RSUs are more effective for CPM dissemination than fixed RSUs. Our results show that the proposed mobile RSU-assisted CPM dissemination mechanism distributes on average 3.7 times more CPM objects to V2X vehicles than fixed RSUs. Moreover, the proposed dynamic CPM generation rate control mechanism maintains overall latency below 100 ms while adapting the CPM generation interval according to the current environment. After confirming the feasibility of using mobile RSUs for CPM dissemination with simulations, we model the proposed system for an n-lane road segment scenario, validating its performance by comparing it with simulation results. Finally, we perform a detailed parameter analysis on the model to evaluate the benefits of the proposed CPM dissemination mechanism across various scenarios.